In Vitro Evaluation of the Antimicrobial Efficacy of Four Endodontic Biomaterials against Enterococcus faecalis, Candida albicans, and Staphylococcus aureus - Nirupama, Duddi Narendra; Nainan, Mohan Thomas; Ramaswamy, Rajendran; Muralidharan, Sethumadhavan; Usha, Hulimangala Hosakote Lingareddy; Sharma, Roshni; Gupta, Soham (International Journal of Biomaterials, 2014)
Root canal sealers that possess good antimicrobial property can prevent residual and recurrent infection and contribute to successful endodontic therapy. This study evaluated the antimicrobial activity of four endodontic sealers, AH Plus, Tubliseal EWT, EndoRez, and iRoot SP, against three different microorganisms, E. faecalis, C. albicans, and S. aureus, by direct contact test. 10 μL microbial suspensions were allowed to directly contact the four endodontic sealers for 1 hr at 37°C. Subsequently microbial growth was measured spectrophotometrically every 30 min for 18 hours. The microbial suspensions were simultaneously tested to determine the antimicrobial effect of components which are capable of diffusing into the medium. The results revealed that AH Plus and iRootSP had significantly higher antimicrobial activity against E. faecalis. AH Plus and Tubliseal EWT showed significantly higher antimicrobial activity against C. albicans and S. aureus compared to iRoot SP and EndoRez. EndoRez showed the least antimicrobial activity against all the three microorganisms. Inhibition of microbial growth is related to the direct contact of microorganisms with the sealers. In conclusion AH Plus had significantly higher antimicrobial activity against E. faecalis, C. albicans, and S. aureus.